Is Migraine an MPV-Related Disease? An Observational Study of Polish Neurological Patients. (6th December 2019) - Brzeźniakiewicz-Janus, Katarzyna; Lancé, Marcus D.; Tukiendorf, Andrzej; Rupa-Matysek, Joanna; Brzozowska-Mańkowska, Sybilla; Franków, Mirosław; Wolny-Rokicka, Edyta; Gil, Lidia
Abstract : Many studies have found correlations between abnormal MPV and clinical reactivity in a variety of diseases. In the present paper, we sought MPV-related neurological diseases that are less frequently reported in the literature. The electronic medical records of 852 neurological patients with mean platelet volume (MPV) measurements (F = 45 %, a g e = 55.7 ± 18.7, 8–104) were searched after the patients had received a diagnosis of a neurological disease (new and old episodes) according to the nine classes of the International Statistical Classification of Diseases and Related Health Problems, 10th revision (ICD-10). A set of consecutive statistical methods (i.e., cluster analysis, segmented regression, linear correlation, propensity score matching, and mixed effects Poisson regression) were used to establish a link between MPV and neurological disease. A statistically significant (p < 0.05 ) relationship with MPV was found only in pain syndrome patients, with seven out of eight clinically diagnosed migraine episodes. With all other ICD-10 classes of neurological diseases, the effect of MPV was found to be nonsignificant (p > 0.05 ). MPV may implicate a clinical relationship with pain syndrome and migraine episodes. More complex statistics could help analyse data and find new correlations.